2003
DOI: 10.2174/1389450033347028
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemoprevention Drug Targets

Abstract: Cancer chemoprevention is a new approach in the management of cancer. Traditional cytotoxic chemotherapeutic approaches cannot cure most advanced solid malignancies. Chemoprevention can be defined as the use of non-cytotoxic drugs and natural agents to block the progression to invasive cancer. Chemoprevention can either prevent DNA damage that initiates the neoplastic transformation process or reverses the progression of pre-invasive lesions. Epidemiological observations, experimental evidence from animal carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Chemoprevention can be defi ned as the application of natural or synthetic molecules to prevent, inhibit, or reverse the carcinogenic machinery ( 113 ). Epidemiologic studies demonstrated that individuals eating more fruits and vegetables that are rich in carotenoids and people having higher serum ␤ -carotene levels have a lower risk of cancer, particularly lung cancer ( 114 ).…”
Section: Biological Activities Of ␤ -Apocarotenoids In Mammalsmentioning
confidence: 99%
“…Chemoprevention can be defi ned as the application of natural or synthetic molecules to prevent, inhibit, or reverse the carcinogenic machinery ( 113 ). Epidemiologic studies demonstrated that individuals eating more fruits and vegetables that are rich in carotenoids and people having higher serum ␤ -carotene levels have a lower risk of cancer, particularly lung cancer ( 114 ).…”
Section: Biological Activities Of ␤ -Apocarotenoids In Mammalsmentioning
confidence: 99%
“…For example, aspirin, other NSAIDS and calcium have demonstrated considerable reductions of risk in colorectal cancer, and NSAIDs have been shown to effectively protect against the development of oesophageal and gastric cancers from their premalignant conditions. 2,3 The mechanisms of chemopreventive effects of NSAIDs may be largely due to inhibition of cyclooxygenase-2 (COX-2), the crucial enzyme in the conversion of arachidonic acid to prostaglandins, whereas the side effects of NSAIDs are largely attributable to the nonspecific inhibition of cyclooxygenase-1 (COX-1). COX-2 is frequently over-expressed in various gastrointestinal malignancies, such as gastric and colon cancers, 4,6 whereas its expression in normal gastric and colonic mucosa is relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…It is being used successfully for the treatment of rheumatoid arthritis, osteoarthritis, acute pain, familial adenomatous polyposis and primary dysmenorrhea. 1,2) Celecoxib also demonstrated significant chemopreventive activity in colon carcinogenesis, ultraviolet B radiation (UVB) induced skin cancer and breast cancer. [3][4][5] Celecoxib is weakly acidic (pK a is 11.1) and hydrophobic (Log P is 3.5) and its low aqueous solubility (3-7 mg/ml) contributes to high variability in absorption after oral administration.…”
mentioning
confidence: 99%